Hydrogen generator from water / Muhammad Hizami Rahman - Rahman, Muhammad Hizami (2023)
As we are aware of, liquefied petroleum, natural gas primarily methane and gas such as butane, propane or a mixture of both gases are commonly used to make a fire for processes including brazing and welding in engineering works. Unfortunately, the price for this type of fuel is considerably expensive and unpractical for using it repeatedly in a process that did not need a lot of fire power. This project is being made to to have a prototype that can generated fire from a resource that can be found easily and cheaper but manage to produce power that can compete with the old fuels. This project is build based on means of separating the 2 particles from the water that is hydrogen and oxygen to using the electrolysis method to create a gas that can form a fire once it is lit. The outcome of this project is to make the product function properly and can be used to weld and brazing.